Wealth and Sedentary Time Are Associated With Dietary Patterns Among Preadolescents in Nairobi City, Kenya - Nils Joseph Swindell (Journal of Nutrition Education and Behavior, 2023)
Objective: The study aimed to compare dietary patterns in preadolescents in urban areas with different physical activity and socioeconomic profiles in Nairobi, Kenya.Design: Cross-sectional.Participants: Preadolescents aged 9−14 years (n = 149) living in low- or middle-income areas in Nairobi.Variables Measured: Sociodemographic characteristics were collected using a validated questionnaire. Weight and height were measured. Diet was assessed using a food frequency questionnaire and physical activity by accelerometer.Analysis: Dietary patterns (DP) were formed through principal component analysis. Associations of age, sex, parental education, wealth, body mass index, physical activity, and sedentary time with DPs were analyzed with linear regression.Results: Three DPs explained 36% of the total variance in food consumption: (1) snacks, fast food, andmeat; (2) dairy products and plant protein; and (3) vegetables and refined grains. Higher wealth was associated with higher scores of the first DP (P < 0.05).Conclusions and Implications: Consumption of foods often deemed unhealthy (eg, snacks and fast food) was more frequent among preadolescents whose families were wealthier. Interventions that seek ways to promote healthy lifestyles among families residing in urban areas of Kenya are warranted.